Stomach Cancer Detection through Exhaled Breath using Biomarkers Analysis - Aylen Lisset Jaimes Mogollon; Cristhian Duran Acevedo; Eduardo Gualdron Guerrero Oscar; Radu Ionescu Septimiu (Chemical Engineering Transactions, 2018)
Normally, when a person is affected by a disease, there is an imbalance in their metabolic system that causes a change in the behaviour of their body. In the case of a person affected by cancer or gastric diseases, the presence of the specific volatile metabolites has been exposed for them, which are useful as markers and allows the early diagnosis of these diseases, which facilitates the adaptation of treatments for the prevention, diagnosis and cure of patient. By using of the gas chromatography it is possible to realize a qualitative and quantitative analysis of the composition of breathing in healthy people or with cancer, which allows to identify biomarkers, so it could be a diagnostic method for such diseases, with the advantages to discriminative rapidly, safety way with a non-invasive method for the early detection of the disease, which can be applied for screening tests to be carried out on populations at risk. This study describes a methodology for the gastric cancer detection through biomarkers in Colombian patients. For the validation of the results obtained, 30 measures were taken from the volunteers, which were stored in Tenax tubes; then they were analysed with a gas chromatography and mass spectrometry equipment. On the other hand, a set of 7 compounds (biomarkers) was found through the analysis of GC-MS, which were related to the metabolism of patients with gastric cancer (GC) and control (C).